Math

posted by .

Find the equation of the tangent to the graph at the indicated point.
f(x) = x^2 − 1; a = 3
and
f(x) = x^2 − 8x; a = −9
whats the difference between 1 and 8x. What formula do I use and how should i solve both of these problems?
Thank you

  • Math -

    Why are you using ""a , as in a = 3 ?
    There is no "a" in either equation

    Is this a "first principle" question to find the equation of the tangent to a curve ?

    I will assume that is the case, and do the 2nd problem, the harder of the two .....

    slope of tangent at x = -9 :

    f(-9) = 81 -8(-9) = 153
    f(-9 +h) = (-9+h)^2 -8(-9+h)
    = 81 - 18h + h^2 +72 - 8h
    = h^2 -26h + 153

    slope
    =lim [ f(-9+h) - f(-9) ]/h , as h ---> 0
    = limit [ (h^2 - 26h + 153) - 153]/h , as h --> 0
    = limit [ h(h - 26 ]/h
    = limi h-26 , as h --> 0
    = -26

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
  2. calculus

    Write the equation of the tangent line to the curve at the indicated point. As a check, graph both the function and the tangent line. f(x) = x7 − 7 at x = −1 7 x7
  3. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  4. Product of Roots of Sums of Products of Difference

    What is the product of all roots to the equation ++(x−1)(x−2)(x−3)+(x−2)(x−3)(x−4)(x−3)(x−4)(x−5)+(x−4)(x−5)(x−6)(x−5)(x−6)(x−7)+(x−6)(x−7)(x−8)=0?
  5. Product of Roots of Sums of Products of Difference

    What is the product of all roots to the equation ++(x−1)(x−2)(x−3)+(x−2)(x−3)(x−4)(x−3)(x−4)(x−5)+(x−4)(x−5)(x−6)(x−5)(x−6)(x−7)+(x−6)(x−7)(x−8)=0?
  6. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  7. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  8. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  9. Calculus

    Sketch a graph of the parabola y=x^2+3. On the same graph, plot the point (0,−6). Note there are two tangent lines of y=x2+3 that pass through the point (0,−6). The tangent line of the parabola y=x^2+3 at the point (a,a^2+3) …
  10. Maths-Calculus

    If f(2)=1 and f(2+h)=(h+1)3, compute f′(2). If f(−1)=5 and f(−0.9)=5.2, estimate f′(−1). If the line y=−3x+2 is tangent to f(x) at x=−4, find f(−4). Your answer should be expressed as …

More Similar Questions